A bank’s strategical positioning within the Green Sector for an increased customer satisfaction : a segmented kano analysis - Klofsten, Oscar (SLU/Dept. of Economics, 2021)
The major banks in Sweden are seen as confusingly similar to their customers. By taking a behavioural focus, banks may understand how they can make themselves unique and increase their customer satisfaction. Through increasing customer satisfaction, banks may be able to gain a competitive advantage and consequently increase their profit. Previous studies have focused on understanding how a bank’s products and services influence customer satisfaction. However, none have investigated how a bank can increase their satisfaction towards customers in the green sector. This study will fill this research gap by identifying how a bank can design its services towards strategic customer segments in the green sector. The application of a segmented Kano analysis is presented: 21 potential offerings were assessed by a sample of 258 responses. The analysis indicates that the “people” category in the service marketing mix has the highest customer satisfaction potential. That the bank’s personnel emphasise a competence, genuine interest, engagement and understanding of the customers’ businesses. The results clearly shows that if the customers feel understood and seen by the bank, the customer satisfaction potential is high. The “price” service marketing mix category seem to have a relative low customer satisfaction potential, however, the strength and customer dissatisfaction potential are high. To match the competitors’ interest rate is therefore of importance, but to do more than matching does not seem to affect customer satisfaction considerably. This study indicates a strong heterogeneity between the investigated strategic customer segments. Customers with a high entrepreneurial orientation are a sensitive segment with potential for being both more satisfied and dissatisfied, depending how actively the bank work with the desired offerings. Additionally highly entrepreneurial customers wish for the bank to give an impression of drive and entrepreneurial focus and that the bank physically visits their business. The large farms differ from the rest of the customers in that their entrepreneurial orientation is significantly higher. Furthermore they put high importance in that the bank physically visits their business and that the bank makes them feel proud being customers and create a sense of belonging. The large forestry owners do not put as much importance in if the bank market itself as a rural bank or the personnel’s background in forestry or agriculture. Lasty, the study shows that the highly profitable customers in the green sector is a difficult group to satisfy. Their dissatisfaction potential is higher for most of the offerings while their satisfaction potential is the same.